The car catalyst-students' misconceptions and how to challenge them - ELENI DAOUTSALI; HANS-DIETER BARKE (Metaichmio Publications, 2011)
The objective of this study was to find out what students already know about the car catalyst in order to design a module to pass on the scientific mental model to them. Therefore a questionnaire was given to students in 9th, 10th and 11th grade pupils. Questions referred to what happens inside a catalyst with the incoming gases. The misconception of a filter or a further combustion engine could be localized. According to the students the catalyst is equipped with netting which slices the molecules. According to the misconceptions received a topic was designed to overcome and cure these concepts and to clarify and give the pupils a valid picture of what happens inside the catalyst. In a post-test results are discussed.